Tenant’s choice of residential property location in Mankweng Township, Polokwane Local Municipality - Alabi, Ijeoma Uchenna (University of Limpopo (Turfloop Campus), 2013)
The aim of the study was to carry out an analysis of the factors influencing tenants’ choice of residential property location in Mankweng Township. The study used both quantitative and qualitative research approaches. The structured questionnaire, interview and documented literature were used to collect data. The data were analysed using the SPSS statistical package and the Excel spread sheet. To this end, specific working objectives were formulated as follows: to identify the types of residential property in the study area, to determine the factors which influence the choice of residential property location in the study area and lastly, to compare the relationships that exist among the residents in Mankweng Township. The results of the research showed that among all the factors marital status, age, household’s size, race, education and income were not among the factors influencing the choice of residential location in Mankweng Township. However, gender, employment status, distance from city centre, hospital, place of worship, security or police station, water and electricity significantly influenced the choice of residential location choice in Mankweng Township. The study therefore recommends government to be more responsive and active in the provision of urban infrastructure and services in every neighbourhood. This will help address the major reason why tenants search for accommodation from one location to another. In addition, real estate investors should consider the availability of infrastructure before choosing a location for community development. Thus, when urban facilities and services are evenly distributed, this may enhance proper development in the community
Thesis (M. Dev.) -- University of Limpopo, 2013
Keywords: Residential property; Tenants; Mankweng township; Rental housing -- South Africa -- Limpopo; Landlord and tenant -- South Africa -- Limpopo; Housing -- South Africa -- Limpopo